IMPLEMENTASI DALAM PRAKTEK PENDAFTARAN JAMINAN FIDUSIA SECARA ELEKTRONIK - Amalia, Tasya; Purba, Hasim; Devi Anwar, Tengku Keizerina (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The Director General of AHU provides a new breakthrough by launching an electronic fiduciary registration system. However, this system is not without problems. Many parties encounter obstacles in electronic fiduciary registration, for example system problems, difficulties in accessing the platform, and some data that is not yet available in the electronic AHU system. The problems in this research are regarding legal responsibility if there is a data input error in the electronic Fiduciary Guarantee registration system, the role of the Notary in carrying out electronic Fiduciary Guarantee registration and the validity of the Fiduciary Guarantee deed which occurs if it is not registered because the server is down in the practice of registering Fiduciary Guarantee electronically. electronic. The conclusion of this research is that the responsibility of a notary who makes data input errors in the electronic Fiduciary Guarantee registration system is limited to the responsibility of correcting the data input errors made, either before or after the PNBP payment is made by the notary. The responsibilities that a notary must carry out in this case do not include administrative, civil or criminal responsibilities. One of the roles of a notary is to make a Fiduciary Guarantee deed, which is a partij deed, namely a deed made before a notary, after which the fiduciary guarantee is registered at the Fiduciary Registration Office. The validity of the Fiduciary Guarantee deed that occurs if it is not registered because the server is down in the practice of registering the Fiduciary Guarantee electronically will not be binding on the parties or third parties, giving rise to legal consequences of the absence of legal certainty and legal protection for interested parties. Keyword: Implementation, Electronic Fiduciary Registration, Notary Abstrak: Dirjen AHU memberikan terobosan baru dengan meluncurkan sistem pendaftaran fidusia secara elektronik. Namun, sistem ini bukan tanpa masalah. Banyak pihak yang menemukan hambatan dalam pendaftaran fidusia secara elektronik ini misalnya gangguan sistem, kesulitan dalam akses platform, serta beberapa data yang belum tersedia pada sistem AHU elektronik. Permasalahan dalam penelitian ini adalah mengenai tanggung jawab hukum jika terjadi kesalahan input data dalam sistem pendaftaran Jaminan Fidusia secara elektronik, peran Notaris dalam melalakukan pendaftaran Jaminan Fidusia secara elektronik dan keabsahan akta Jaminan Fidusia yang terjadi jika tidak didaftrakan karena server down dalam praktek pendaftaran Jaminan Fidusia secara elektronik. Kesimpulan penelitian ini adalah tanggung jawab notaris yang melakukan kesalahan input data dalam sistem pendaftaran Jaminan Fidusia secara elektronik hanya sebatas tanggung jawab pembetulan terhadap kesalahan input data yang dilakukan, baik itu sebelum atau setelah pembayaran PNBP dilakukan oleh notaris. Tanggung jawab yang harus diemban oleh notaris dalam hal ini, bukan termasuk tanggung jawab dalam bentuk administratif, perdata maupun pidana. Salah satu peran notaris adalah membuat akta Jaminan Fidusia, yang merupakan akta partij yakni akta yang dibuat di hadapan notaris, untuk selanjutnya dilakukan pendaftaran jaminan fidusia ke Kantor Pendaftaran Fidusia. Keabsahan akta Jaminan Fidusia yang terjadi jika tidak didaftarkan karena server down dalam praktek pendaftaran Jaminan Fidusia secara elektronik adalah tidak akan mengikat bagi para pihak maupun pihak ketiga, sehingga menimbulkan akibat hukum tidak adanya kepastian hukum dan perlindungan hukum bagi pihak yang berkepentingan.  Kata kunci: Implementasi, Pendaftaran Fidusia Elektronik, Notaris